2018
DOI: 10.1007/s00404-018-4754-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of complement components C1q, MBL and C1 inhibitor in pathogenesis of endometriosis

Abstract: PurposeThe purpose of the work was to evaluate possible associations between the complement components C1q, mannose-binding lectin (MBL) and C1 inhibitor (C1INH) with pathogenesis of endometriosis.MethodsConcentrations of C1q, MBL and C1INH were measured by ELISA in peritoneal fluid (PF) in 80 women with or without endometriosis.ResultsSignificantly higher PF levels of C1q, MBL and C1INH in women with endometriosis compared to control group were observed (p < 0.0001). A higher concentration of the studied para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…The presence of complement component (C4) and complement activation products (C3c SC5b-9) in the PF and in the sera of EM women have been previously described (38). Significantly higher PF levels of C1q, MBL and C1-INH in women with EM compared to control group has also been reported (39).…”
Section: Discussionmentioning
confidence: 84%
“…The presence of complement component (C4) and complement activation products (C3c SC5b-9) in the PF and in the sera of EM women have been previously described (38). Significantly higher PF levels of C1q, MBL and C1-INH in women with EM compared to control group has also been reported (39).…”
Section: Discussionmentioning
confidence: 84%
“…Swati et al revealed that chronic inflammation in endometriosis is dominated by complement 7 . Sikora et al had proved that abnormal activation of the complement pathway occurred in EMS and resulted in the overexpression of C1Q, MBL, C1INH 36 . In our study, we found that the up-regulated expression of the central complement factor (C1S, C1QA, C1R, and C3) in EMS, indicating that the abnormal status of complement might be involved in the pathogenesis of EMS.…”
Section: Discussionmentioning
confidence: 99%
“…We observed increased levels of C3a in the peritoneal fluid of EM patients ( 118 ); Kabut et al ( 119 ) have also reported increased levels of C3c, C4, and sC5b-9 in the peritoneal fluid and serum of EM patients in comparison with healthy women. A recent study reported significantly higher concentrations of C1q, MBL and C1-INH in the peritoneal fluids of EM women as compared to the control group ( 120 ). No difference in plasma C3a levels between women with and without EM was found ( 121 ).…”
Section: Complement In Endometriosis Peritoneal Fluidmentioning
confidence: 93%